Sophomores and other oxymorons : another novel - Lubar, David (New York, New York : Dutton Books, an imprint of Penguin Random House LLC, 2015)
Following a difficult freshman year, Scott Hudson is hoping that sophomore year will be easier, but after a disaster of a first week he finds himself faced with new challenges--including a particularly demanding English teacher, a school board member whose budget cutting is covering up a crime, and the discovery that his friendship with Lee, the Goth girl he met last year, is turning into something else entirely.
Sequel to: Sleeping freshmen never lie.
Tặng
Keywords: Conduct of life -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Families -- Pennsylvania -- Juvenile fiction; Friendship -- Juvenile fiction; High schools -- Juvenile fiction; Self-confidence -- Juvenile fiction; Conduct of life -- Fiction; Dating (social customs) -- Fiction; Family life -- Pennsylvania -- Fiction; Friendship -- Fiction; High schools -- Fiction; Schools -- Fiction; Self-confidence -- Fiction; Pennsylvania -- Juvenile fiction; Pennsylvania -- Fiction